Cellular Metabolism and Its Effect on the Type III Secretion System of Dickeya Dadantii 3937 - (:unkn) unknown (My University, 2013)
Nutrition, in both eukaryotes and prokaryotes, is vital to the life and well-being of the species. In organisms such as Escherichia coli, metabolism and its regulation have been well established, whereas in Dickeya dadantii 3937, the metabolic pathways and their effects on other processes have not been elucidated. Little is known is how carbon metabolism is able to regulate virulence and pathogenicity in this organism. In this work, we have investigated how the metabolic network contributes to positively and negatively regulating the pathogenicity of Dickeya dadantii 3937. Chapter 1 provides an overview of the history and virulence processes in the organism. In Chapter 2, Dickeya dadantii 3937 was tested in different carbon sources for its ability to induce the type III secretion system (T3SS). Dickeya dadantii 3937 was able to express the T3SS in carbon sources that are upstream of the dihydroxyacetone phosphate/glyceraldehyde-3-phosphate conversion point in the Embden-Meyerhof-Parnas pathway of glycolysis. A mutation was made in the pgi gene, which encodes phosphoglucoisomerase, critical for the conversion of glucose-6-phosphate to fructose-6-phosphate. The pgi mutant had reduced expression of hrpL (the master regulator of T3SS expression), hrpA (the type III secretion pilus), and rpoN (the nitrogen-related sigma factor) genes, but increased expression of gcpA (diguanylate cyclase), in comparison to the wild-type strain. Fructose-6-phosphate supplementation restored T3SS gene expression to near wild-type levels. Complementation of the pgi mutant with the pgi gene restored swimming, swarming, in vivo virulence, and expression of T3SS genes. These results suggest that the metabolic gene pgi, and its intermediate fructose-6-phosphate, may indirectly play a role in the expression of virulence factors in Dickeya dadantii 3937. In Chapter 3, a mutant of Dickeya dadantii 3937was produced by a miniHimar Tn5 RB1 transposon insertion. This mutant was unable to grow on minimal media with fructose. The insertion mapped to a 1,650bp gene product, which sequenced to the fruA gene, which corresponds to the fructose permease, which is the sugar transport component of the fructose phosphotransferase system (PTS). This mutant had increased hrpS, hrpL, and hrpA gene transcription. A fruB mutant showed slightly decreased T3SS activity, but fruB overexpression in the wild-type, and complementation in the fruB mutant showed increased hrpS expression. The FruB protein also interacted with HrpX at the protein level using a yeast two-hybrid assay, showing increased â-galactosidase activity in comparison to empty vector control, HrpX, and FruB alone. This suggests that the fructose PTS plays a part in regulating the T3SS of Dickeya dadantii 3937.
Keywords: Metabolism; Phosphotransferase System; PTS; T3SS